OsARF4 regulates leaf inclination via auxin and brassinosteroid pathways in rice - Qiao, Jiyue; Zhang, Yanjun; Han, ShaqiLa; Chang, Senqiu; Gao, Zhenyu; Qi, Yanhua; Qian, Qian (Frontiers in Plant Science, 2022)
Leaf inclination is a vital agronomic trait and is important for plant architecture that affects photosynthetic efficiency and grain yield. To understand the molecular mechanisms underlying regulation of leaf inclination, we constructed an auxin response factor (arf) rice mutant—osarf4—showing increased leaf inclination using CRISPR/Cas9 gene editing technology. OsARF4 encodes a nuclear protein that is expressed in the lamina joint (LJ) at different developmental stages in rice. Histological analysis indicated that an increase in cell differentiation on the adaxial side resulted in increased leaf inclination in the osarf4 mutants; however, OsARF4-overexpressing lines showed a decrease in leaf inclination, resulting in erect leaves. Additionally, a decrease in the content and distribution of indole-3-acetic acid (IAA) in osarf4 mutant led to a greater leaf inclination, whereas the OsARF4-overexpressing lines showed the opposite phenotype with increased IAA content. RNA-sequencing analysis revealed that the expression of genes related to brassinosteroid (BR) biosynthesis and response was different in the mutants and overexpressing lines, suggesting that OsARF4 participates in the BR signaling pathway. Moreover, BR sensitivity assay revealed that OsARF4-overexpressing lines were more sensitive to exogenous BR treatment than the mutants. In conclusion, OsARF4, a transcription factor in auxin signaling, participates in leaf inclination regulation and links auxin and BR signaling pathways. Our results provide a novel insight into l leaf inclination regulation, and have significant implications for improving rice architecture and grain yield.